Penerapan Model Pembelajaran Learning Cycle 5e Sebagai Upaya Untuk Meningkatkan Kemampuan Komunikasi Matematis Siswa - Yuniarti, Nia; Murnaka, Nerru Pranuta (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2017)
Mathematical communication ability is an important ability to have students. This is because by having these abilities, students can communicate ideas or mathematical ideas both orally and in writing. However, based on preliminary studies in the form of mathematical communication and class observation tests conducted by researchers in one class at SMP Negeri 8 Kota Tangerang Selatan showed that students' mathematical communication ability is still low. The efforts that can be done is to apply a model of learning that can train and cultivate students' mathematical communication ability by applying the learning cycle 5e model. The purpose of this study is to determine whether the average of improvement mathematical communication skills of students who get a learning model learning cycle 5e higher than students who obtain conventional learning. This type of research is quasi experiment. The research design used is a nonequivalent control group design. The population in this research are the students of class VII.1, VII.2, and VII.3 SMP Negeri 8 Kota Tangerang Selatan and the sample is the students of class VII.2 as the experimental class and class VII.3 as the control class. The sampling technique used random cluster sampling. Hypothesis testing of research done by the parametric test (t-test). In this research, it can be concluded that the average improvement mathematical communication ability of students who get the learning cycle 5e model is higher than students who get conventional learning. Keywords: Mathematical communication skill, learning cycle 5e model, quasi-experiment